Thumbs up for new millet - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
A new variety of millet developed by Burkina Faso s agricultural research institute, l Institut national pour l étude et la recherche agronomique (INERA), is proving a big hit with farmers in the central southern region of the country. ..